PENGARUH BUDAYA ORGANISASI DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PT POS INDONESIA (PERSERO) KANTOR POS BATURAJA 32100 - Hema Malini (KOLEGIAL, 2017)
The purpose of this study was to determine the influence of organizational culture and job training on employee performance PT Pos Indonesia (Persero) Post Office Baturaja 32100. This research is an explanation research with a population of 30 employees. Using multiple regression analysis techniques and for testing the research hypothesis, F-test and t-test were used. From result of calculation, got result that: 1) value of organizational culture coefficient equal to 0,470 (47%),; 2) The coefficient value of job training amounted to 0.361 (36.1%), mean organizational culture and job training affect employee performance. From result of hypothesis test t, got result as follows: 1) tcount (2,156)> ttable (2.052) means There is influence of Organization Culture to Employee Performance; 2) The value of tcount (2.082)> ttable (2.052) which means that there is the influence of Job Training on Employee Performance. While the results of hypothesis F test, obtained the value of Fhitung (21.212)> Ftabel (3.35), this means that the variable Organizational Culture and Job Training variables together there is a significant influence on Employee Performance.